Integrated Traditional Chinese and Western medicine nursing of a patient with pneumonia caused by Chlamydia psittaci (1例鹦鹉热衣原体肺炎患者的中西医结合护理体会) - HU Fangxia (胡芳霞); ZHANG Yan (张艳) (Journal of International Translational Medicine Limited, 2024)
This article summarizes the integrated Traditional Chinese and Western medicine nursing of a patient with pneumonia caused by Chlamydia psittaci. A comprehensive nursing risk assessment was carried out, followed by the dietary nursing, body temperature monitoring, emotional care and other basic nursing interventions. Based on the concept of Traditional Chinese Medicine syndrome differentiation, Traditional Chinese Medicine nursing techniques such as auricular acupoint pressing and acupoint application therapy were carried out to control the infection, improve the immunity of the patient and accelerate the rehabilitation. (本文总结1例鹦鹉热衣原体肺炎患者的中西医结合护理经验。基于护理评估和中医辨证施护, 在饮食护理、体温护理、情志护理等常规干预基础上, 给予耳穴压丸调理脏腑、穴位贴敷止咳中医护理适宜技术, 有效控制肺部感染, 提高患者免疫力, 促进患者康复。)